Evaluation Of P2tl Operation Digitalization: Analysis Of Factors Affecting Digitalization Effectiveness And Its Impact On P2tl Performance At Pln Uid Kaltimra - Wunas, Gitta Angelina; Mulyono Azis , Anton (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
PLN continues to adapt to technological developments through digital transformation strategies designed to improve operational efficiency and support key performance indicator (KPI) achievement. One operational process is Electricity Usage Control (P2TL) which directly contributes to company KPIs. In mid-2024, PLN UID KALTIMRA implemented the Efficiency Program Monitoring (EPM) application as digitalization to enhance customer inspection effectiveness and monitor field officer performance. Despite expectations that EPM would improve P2TL effectiveness, field findings showed decreased inspection results. This study aims to analyze factors influencing EPM implementation effectiveness and its impact on P2TL kWh realization and job satisfaction. Using a quantitative approach with case study strategy and survey design, primary data was collected through questionnaires to all field officers and relevant staff, while secondary data came from PLN UID KALTIMRA internal reports, analyzed using Structural Equation Modeling (SEM). Results show that application stability, process-technology fit, and user-friendliness positively affect digitalization effectiveness, while management support has no significant effect. EPM implementation effectiveness significantly affects job satisfaction but does not influence P2TL kWh realization improvement. This indicates that digitalization success depends not only on technology adoption but also on process alignment and user engagement.